2021
DOI: 10.1172/jci.insight.145256
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution microscopy reveals photoreceptor-specific subciliary location and function of ciliopathy-associated protein CEP290

Abstract: Mutations in the cilium-associated protein CEP290 cause retinal degeneration as part of multi-organ ciliopathies or as retina-specific diseases. The precise location and the functional roles of CEP290 within cilia and, specifically, the connecting cilia (CC) of photoreceptors, remain unclear. We used superresolution fluorescence microscopy and electron microscopy (TEM) to localize CEP290 in the CC and in primary cilia of cultured cells with sub-diffraction resolution, and to determine effects of CEP290 deficie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 83 publications
(129 reference statements)
0
27
0
Order By: Relevance
“…Moreover, we demonstrated that CEP290 setup and maintenance in the CC are independent of the CC inner scaffold, revealing that different modules can be discriminated inside the CC. Consistently, Potter and colleagues showed that Cep290 -knockout photoreceptors still possess the CC inner scaffold protein CENTRIN, suggesting that CEP290 and the CC inner scaffold are probably independent [ 20 ]. These results suggest that the CC might differ from a long canonical TZ, as previously suggested.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, we demonstrated that CEP290 setup and maintenance in the CC are independent of the CC inner scaffold, revealing that different modules can be discriminated inside the CC. Consistently, Potter and colleagues showed that Cep290 -knockout photoreceptors still possess the CC inner scaffold protein CENTRIN, suggesting that CEP290 and the CC inner scaffold are probably independent [ 20 ]. These results suggest that the CC might differ from a long canonical TZ, as previously suggested.…”
Section: Discussionmentioning
confidence: 94%
“…We next investigated the precise localization of the inner scaffold components POC5, CENTRIN, and FAM161A in adult mouse photoreceptors, with the exception of POC1B owing to the lack of appropriate antibodies. We also inspected the distribution of CEP290, known to localize along the CC from super-resolution microscopy [ 20 ], and Lebercilin (LCA5), a proposed FAM161A interactor [ 10 ], mutations in which have been linked to Leber congenital amaurosis, a retinopathy causing severe visual deficiency from the first year after birth [ 21 , 22 ]. Consistent with our previous work, all 3 inner scaffold proteins were found in the central core region of centrioles, where the inner scaffold structure lies [ 16 ] ( Fig 1C–1E ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ciliary protein CEP290 localises to the TZ in photoreceptor cilia and is known to interact with RPGR [ 31 , 32 ]. In both control 30-week-old iPSC-ROs, there was strong co-localisation of CEP290 and RPGR at the photoreceptor TZ ( Figure 5 D(i) and Supplementary Figure S4A , white arrows, yellow co-stain in merged images).…”
Section: Resultsmentioning
confidence: 99%
“…To gain a better understanding of CEP290-LCA, many aspects of CEP290 cell biology have been extensively studied. Combined, these studies suggest that CEP290 influences both ciliogenesis 4,5 and ciliary protein content by acting as a gatekeeper in protein trafficking through the connecting cilium that normally bridges the inner and outer segment of photoreceptors 68 . CEP290 mutations can preclude the ability for normal outer segments to form and cause an accumulation of proteins typically in the outer segment, such as rhodopsin, within the inner segment 6 .…”
Section: Introductionmentioning
confidence: 94%